Three new species of Lachesilla in the rufa group (Psocodea: Psocomorpha: Lachesillidae) from the Sierra Tarahumara, Mexico - Aldrete, Alfonso Neri García; Casasola-González, José Arturo (Zootaxa, 2021)
Three species of Lachesilla, in species group rufa, from the Sierra Tarahumara, Chihuahua, Mexico, are here described and illustrated: L. byei n. sp., L. furthi n. sp., and L. raramuri n. sp. Two of them belong in Subgroup IIb of the species group, one showing affinities with L. sommermanae García Aldrete and L. yakima Mockford & García Aldrete, the second one showing affinity with L. salamana García Aldrete. The third species belongs in Subgroup I of the species group, showing affinities with L. aspera García Aldrete and L. chiricahua García Aldrete. The especies here described raise to seven the number of species of Lachesilla in the Sierra Tarahumara.